Pengaruh Kualitas Laporan Keuangan, Peranan Sistem Informasi Akuntansi, Sistem Pengendalian Internal Dan Efisiensi Tenaga Kerja Terhadap Kinerja ManajerialnKencana - Luis Andreas; Sunarji Harahap; Elidawati Elidawati; Thomas Sumarsan Goh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research was conducted at Kencana. The purpose of this study was to analyze the influence of the quality of financial statements, the role of accounting information systems, internal control systems and labor efficiency affect the managerial performance of Kencana. The population and sample in this study were 47 financial employees of Kencana. Sampling technique used is census sampling. Data collection techniques are by distributing questionnaires, interviews and documentation studies. Data analysis using an multiple linear regression analysis. Conclusion in the study that simultaneously and partial the quality of financial statements, the role of accounting information systems, internal control systems and labor efficiency have a positive and significant effect on the managerial performance of Kencana. While partially the quality of financial statements.